Prevalence of seroadaptive behaviours of men who have sex with men, San Francisco, 2004. Issue 6 (7th June 2009) - Snowden, J M; Raymond, H F; McFarland, W
Abstract : Objectives: To define and measure the prevalence of HIV seroadaptive behaviours among men who have sex with men (MSM). Methods: A community-based, cross-sectional sample of 1211 HIV negative and 251 HIV positive MSM was recruited in San Francisco in 2004 by time-location sampling. Seroadaptive behaviours were defined by enumerating and characterising all episodes of anal intercourse by partner type, partner HIV serostatus, sexual position and condom use for up to five partners in the preceding 6 months. Results: Among HIV negative MSM, 37.6% engaged in some form of apparent seroadaptive behaviour, predominantly pure serosorting (24.7%), followed by seropositioning (5.9%), condom serosorting (3.9%) and negotiated safety (3.1%). Among HIV positive men, 43.4% engaged in some form of seroadaptation, including pure serosorting (19.5%), seropositioning (14.3%) and condom serosorting (9.6%). Consistent condom use was reported by 37.1% of HIV negative and 20.7% of HIV positive MSM. Conclusions: In aggregate, seroadaptive behaviours appear to be the most common HIV prevention strategy adopted by MSM in San Francisco as of 2004. Surveillance and epidemiological studies need to precisely measure seroadaptive behaviours in order to gauge and track the true level of HIV risk in populations. Rigorous prevention research is needed to assess the efficacy of seroadaptive behaviours on individuals' risk and on the epidemic.